PENINGKATAN KEMAMPUAN MENULIS PUISI BERDASARKAN MEDIA CATATAN HARIAN MELALUI MODEL PEMBELAJARAN KONTEKSTUAL SISWA KELAS XII SMA TAMANSISWA PALEMBANG - Mariam Agustina (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2017)
This study aims to improve the ability to write poetry based on daily logs through the contextual learning model of students of class XII IPA Tamansiswa High School of Palembang. This research uses classroom action research type. The research data was taken through tests and nontes. Results of observation on the first cycle student activity percentage 56.97% and increased in cycle II to 79.55%. Increased 22.58%. Similarly with the results of learning activities cycle I, the average grade of 66.8% of students who have completed 17 students or 54.8%, which has not completed 14 students or 45.2%. Based on the results of reflection on the first cycle there are some things that need attention and improvement, then this research needs to proceed with the action cycle II to obtain the desired results. In the second cycle action the results achieved by the average student class 77.6 and all students have been completed or 100% of students have achieved the value of the established KKM. The conclusion of this research that based on the daily diary through contextual learning model can improve students' poetry writing ability and can be an alternative choice for teachers in learning to write poetry.